Impact of Uganda’s National Agricultural Advisory Services program - Benin, Samuel; Nkonya, Ephraim M.; Okecho, Geresom; Randriamamonjy, Josee; Kato, Edward; Lubadde, Geofrey; Kyotalimye, Miriam; Byekwaso, Francis (International Food Policy Research Institute, 2011)
In Uganda, agricultural extension has been hotly debated since the implementation of the National Agricultural Advisory Services (NAADS) program in 2001. Conceived as a demand-driven approach and largely publicly funded with services provided by the private sector, the NAADS program targets the development and use of farmer institutions. It is a key strategy in the government’s poverty-reduction and national development plan. Due to methodological challenges arising from the complex ways that many factors influence the relationship between extension inputs and outcomes, as well as data-quality issues, the effectiveness of agricultural extension in raising agricultural productivity and incomes and reducing poverty is often viewed with skepticism among policymakers and development practitioners. The NAADS program has been no exception. Some initial evaluations, mostly qualitative in nature, indicate the program has had a favorable effect on increasing the use of improved technologies, marketed output, and wealth status of farmers receiving services from the program. However, the program does not appear to be promoting improved soil-fertility management, raising concern about the sustainability of potential productivity increases. Now that the first phase of the program has ended, this study rigorously assesses the outcomes and impacts obtained thus far, in order to help inform the current second phase and offer lessons for others implementing or planning to implement demand-driven agricultural advisory services in developing countries. The findings presented here are useful to policymakers of central and local governments, farmer groups, advisory service providers, donors, and others seeking to improve agricultural extension services in Uganda and elsewhere. Program evaluators and policy analysts will find the methods instructive.